2020
DOI: 10.1111/and.13921
|View full text |Cite
|
Sign up to set email alerts
|

Buried penis in adults as a complication of circumcision: Surgical management and long‐term outcomes

Abstract: We aimed to evaluate the feasibility and long‐term functional outcomes of surgical correction of adult buried penis patients due to complications of childhood circumcision. A retrospective analysis was performed for patients who underwent treatment for buried penis between 1997 and 2019. An autologous split‐thickness skin graft (STSG) was used. Surgical management steps included circumcision, resection of the bands between the corpora and other tissues, harvesting of STSG from femoral region and graft applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…1. After screening 170 records, 21 full-text studies published between 2016 and 2021 were included in the qualitative analysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. All were single-centre retrospective case series.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1. After screening 170 records, 21 full-text studies published between 2016 and 2021 were included in the qualitative analysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. All were single-centre retrospective case series.…”
Section: Search Resultsmentioning
confidence: 99%
“…Three out of 10 studies used an ad hoc-created questionnaire. Author self-impression judgement was applied in most of the studies [11,13,14,15,17,19,21], while only Ghanem et al used the Likert scale [26]. Overall, a notable improvement in cosmetic function was detected.…”
Section: Functional Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently no validated patient-reported outcome measure for patients undergoing AABP repair. Several studies have implemented various patient-reported questionnaires, including the International Index of Erectile Function, 4,7,9,35 the Changes in Sexual Functioning Questionnaire, 8 and the Sexual Satisfaction Scale. 35 As these are not questionnaires specific to AABP, is not clear whether the symptoms reported on these measures were directly attributable to AABP, and they may be confounded by other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implemented various patient-reported questionnaires, including the International Index of Erectile Function, 4,7,9,35 the Changes in Sexual Functioning Questionnaire, 8 and the Sexual Satisfaction Scale. 35 As these are not questionnaires specific to AABP, is not clear whether the symptoms reported on these measures were directly attributable to AABP, and they may be confounded by other conditions. Moreover, despite the highly variable presentation of AABP, many of these questionnaires query only sexual function and do not address other functional limitations that arise as a result of this condition, including pain with ambulation, micturition difficulties, hygiene concerns, recurrent infections, and dissatisfaction with appearance.…”
Section: Discussionmentioning
confidence: 99%